Modular Hybrid Robots For Safe Human-Robot Interaction - J. Radojicic; D. Surdilovic; G. Schreck (Zenodo, 2009)
The paper considers a novel modular and intrinsically safe redundant robotic system with biologically inspired actuators (pneumatic artificial muscles and rubber bellows actuators). Similarly to the biological systems, the stiffness of the internal parallel modules, representing 2 DOF joints in the serial robotic chains, is controlled by co-activation of opposing redundant actuator groups in the null-space of the module Jacobian, without influencing the actual robot position. The decoupled position/stiffness control allows the realization of variable joint stiffness according to different force-displacement relationships. The variable joint stiffness, as well as limited pneumatic muscle/bellows force ability, ensures internal system safety that is crucial for development of human-friendly robots intended for human-robot collaboration. The initial experiments with the system prototype demonstrate the capabilities of independently, simultaneously controlling both joint (Cartesian) motion and joint stiffness. The paper also presents the possible industrial applications of snake-like robots built using the new modules. : {"references": ["Vukobratovi\u0107 M., Surdilovi\u0107 D., Ekalo Y., Katic D., Dynamics and\nRobust Control of Robot-Environment Interaction, World-Scientific,\nNew-Jersey, 2009.", "Chiaverrini S., Siciliano B., Villani L., 1999, A Survey of Robot\nInteraction Control Schemes with Experimental Comparison,\nIEEE/ASME Trans. on Mechatronics, Vol. 4, No. 3, 273-285.", "Sami Haddadin, Alin Albu-Sch\u251c\u00f1ffer and Gerd Hirzinger: The Role of the\nRobot Mass and Velocity in Physical Human-Robot Interaction - Part I:\nUnconstrained Blunt Impacts, IEEE Int. Conf. on Robotics and\nAutomation (ICRA 2008), Pasadena, USA, 2008.", "Dongjun Shin, Irene Sardeliti and Oussama Khatib:A Hybrid Actuation\nApproach for Human-Friendly Robot Design, IEEE Int. Conf. on\nRobotics and Automation (ICRA 2008), Pasadena, USA, 2008.", "Albu-Sch\u251c\u00f1fer A., Eiberger O., Grebenstein M., Haddadin S., Ott C.,\nWimb\u00f6ck T., Wolf S. and Hirzinger G., : \u00d4\u00c7\u00d7Soft Robotics\", IEEE\nRobotics & Automation Magazine, September 2008, pp. 20-26.", "Bicchi A., Tonnieti G., \"Fast and \"Soft-Arm\" Tactics\", IEEE\nRobotics&Automation Magazine, June 2004, pp.22-33.", "J. P. Merlet, Parallel Robots (Solid mechanics and its Applications),\n2end ed., Springer-Verlag, 2006.", "B. Tondu, V. Boitier, P. Lopez. Natural compliance of robot-arms based\non McKibben artificial muscle actuators. In European Robotics and\nIntelligent Systems Conference, pp. 783-797, Malaga, 1994.", "Daerden F., Conception and Realization of Pleated Pneumatic Artificial\nMuscles and Their Use as Compliant Actuation Elements, PhD. Thesis,\nVrije, Universiteit Brussel, 1999.\n[10] Radojicic J., Surdilovic D. and Kr\u251c\u255dger J., \"Control Algorithms of\nPneumatic-Muscles Actuators in Complex Mechanical Chains\", CD\nProc. III Int. Symp. on Adaptive Motion in Animals and Machines,\nAMAM-2005, Sep. 2005, Ilmenau, Germany, Abs. pp 44."]}